3-Hydroxy-3-methylglutaryl CoA reductase of Hevea latex: The occurrence of a heat-stable activator in the C-serum - Mohd. Isa, Ramli B.; Sipat, A.B. (Elsevier BV, 1982)
The effect of the C-serum (the cytosol) on the activity of 3-hydroxy-3-methylglutaryl CoA reductase in the latex of Hevea brasiliensis was investigated. Depending on the clone from which the latex was obtained, the C-serum was found to depress or activate or have little effect on the enzyme activity. Boiling the C-serum however, resulted in a consistent activation effect in all the clones examined. Optimal activation was obtained with 20 μl boiled C-serum. Dialysis or EDTA (40 mM) treatment of the boiled C-serum did not diminish the activation effect. Although not essential, dithiothreitol complemented the activation effect of the boiled C-serum and the optimal concentration was 10 mM. Trypsin digestion of the boiled C-serum resulted in the complete loss of the activation effect. The activator in the boiled C-serum was salted out by ammonium sulphate at 25 - 100% saturation. Hevein had no effect on reductase activity.